Intravascular Papillary Endothelial Hyperplasia (Masson's Tumor) Within Cauda Equina. (November 2018) - Tanaka, Masahiro; Hiyama, Akihiko; Sakai, Daisuke; Katoh, Hiroyuki; Sato, Masato; Watanabe, Masahiko
Abstract : Objective: To describe a rare case of intravascular papillary endothelial hyperplasia (IPEH), also called as Masson's tumor, in a patient with the cauda equina syndrome presenting with low back pain and leg pain. Summary of Background Data: There are no studies that have reported a case of IPEH within the cauda equina. Methods: A 40-year-old man with no prior medical history presented with low back pain and leg pain beginning approximately 5 years ago and a month ago, respectively. MRI revealed a mass at the L2-L3 level that was isointense on T1-weighted images and hypointense with partial areas of high signal intensity on T2-weighted images. A myelogram demonstrated an intradural lesion without any respiratory fluctuation of tumor position, thereby suggesting a metastatic lesion; however, no abnormalities were found on a full-body CT scan or serum investigations for tumor markers. Therefore, surgery was performed on the lesion, within the cauda equina, for diagnosis as well as treatment. Results: Histopathological examination of the excised tumor indicated IPEH. The symptoms and quality of life improved postoperatively; there was no recurrence of the lesion. Conclusion: This is the first report of an IPEH intradural lesion within the cauda equina. Study Design: Case report